Are Cannabis, Cannabis-Derived Products, and Synthetic Cannabinoids a Therapeutic Tool for Rheumatoid Arthritis? A Friendly Summary of the Body of Evidence. Issue 2 (20th March 2022) - Schulze-Schiappacasse, Clara; Durán, Josefina; Bravo-Jeria, Rocío; Verdugo-Paiva, Francisca; Morel, Macarena; Rada, Gabriel
Abstract : Background: Symptom management in rheumatoid arthritis (RA) remains a complex challenge. Widespread use of cannabis-based medicines for a myriad of symptoms has fostered rheumatology patients' interest. However, their safety and efficacy in RA remain unclear. Objective: The aim of this study was to perform a structured summary of the body of evidence in order to determine whether cannabis, cannabis-derived products, and synthetic cannabinoids are an effective treatment for rheumatoid arthritis. Methods: An electronic search in Epistemonikos database was performed to identify systematic reviews and their primary studies that addressed our clinical question. The body of evidence was collected in a pivot table in Epistemonikos. Information and data from the primary studies were extracted from the identified reviews. Finally, extracted data were reanalyzed, and a summary of findings table was generated using the Grading of Recommendations Assessment, Development and Evaluation approach. Results: Twenty-six systematic reviews were identified which included in total only 1 randomized trial assessing our clinical question. Conclusions: Cannabis, cannabis-derived products and synthetic cannabinoids may slightly reduce disease activity in patients with RA. Its use may result in little to no difference in pain reduction and may slightly increase nervous system adverse events. The evidence is very uncertain about the effect of cannabis, cannabis-derived products, and synthetic cannabinoids on serious adverse events risk.